SOCIOLOGY OF COLONIALISM - Palat, Ravi (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
We approach these issues primarily through an analysis of the representations of power and the power of representation. After charting the broad contours of the differences and similarities in colonial formations, we investigate the depiction of colonized people in popular cultural tropes and how these representations have shaped the ways in which the colonizers have portrayed themselves. Intertwined with these representations are the counter-colonial contestations invoked by colonized peoples as they resist colonial domination. We will also examine how patterns of colonial rule, activities of indigenous collaborators, changes in the organization of production, introduction of new plants, animals, and diseases, and labour migrations have transformed colonized societies. Central to all these discussions is a concern with the gendered and racist ideology of colonization—themes that also reverberate in the anticolonial insurgencies and liberation movements.